2018
DOI: 10.1002/mp.12863
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐energetic cross‐talk in photon counting detectors: Numerical detector model (PcTK) and workflow for CT image quality assessment

Abstract: We have developed a new PCD model for spatio-energetic cross-talk and correlation between PCD pixels. The workflow demonstrated the utility of the model for general or task-specific image quality assessments for the PCD- CT.Note: The program (Pc TK) and the workflow scripts have been made available to academic researchers. Interested readers should visit the website (pctk.jhu.edu) or contact the corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Two other models described in the literature include a small sphere with radius 15 lm at 70 keV, where the radius grows as a cube root of the energy, 29 and a larger sphere with radius 50 lm at 60 keV that linearly increases to a radius of 75 lm at 120 keV, 30 but other models also exist. 25 An experimental study found the best fit with a Gaussian charge cloud with r = 30 lm, which is slightly better than our choice of 40 lm. 24 All of these models are simplifications.…”
Section: B Monte Carlo Simulationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Two other models described in the literature include a small sphere with radius 15 lm at 70 keV, where the radius grows as a cube root of the energy, 29 and a larger sphere with radius 50 lm at 60 keV that linearly increases to a radius of 75 lm at 120 keV, 30 but other models also exist. 25 An experimental study found the best fit with a Gaussian charge cloud with r = 30 lm, which is slightly better than our choice of 40 lm. 24 All of these models are simplifications.…”
Section: B Monte Carlo Simulationsmentioning
confidence: 60%
“…While we chose to use in-house Monte Carlo codes for this work, an open-source toolkit that implements a similar approach has recently been made available. 25 Alternatives to Monte Carlo have also been demonstrated that may improve the computational efficiency of simulation. 26 Cascaded systems analysis, in particular, is an efficient method that can also generate theoretical insights on the limiting contributors to dose efficiency.…”
Section: B Monte Carlo Simulationsmentioning
confidence: 99%
“…Almost all of n-tuple counting does not involve neighboring pixels because (a) the probability of triple-and quadruple-counting is less than 1.5% (see Table I of Ref. [12]); and (b) the probability of triple-and quadruple-counting at a pixel boundary is even smaller. Thus, most of spill-in events produce one count at the output-pixel-of-interest, while producing another count at a neighboring pixel.…”
Section: Discussionmentioning
confidence: 99%
“…The PcTK has been extensively evaluated by a Monte Carlo simulator in Ref. [12], while the agreement between the Monte Carlo simulator and an actual PCD has been evaluated in Ref. [13].…”
Section: A Normalized Covariance Matrix Of Neighboring 3 3 3 Pixelsmentioning
confidence: 99%
See 1 more Smart Citation